Structural basis for transfer RNA mimicry by a bacterial Y RNA - Wang, Wei (Structure, 2018)
Noncoding Y RNAs are present in both animal cells and many bacteria. In all species examined, Y RNAs tether the Ro60 protein to an effector protein to perform various cellular functions. Recently, a new Y RNA subfamily was identified in bacteria. Bioinformatic analyses of these YrlA (Y RNA-like A) RNAs predict that the effector-binding domain resembles tRNA. We present the structure of this domain, the overall folding of which is strikingly similar to canonical tRNAs. The tertiary interactions that are responsible for stabilizing tRNA are present in YrlA, making it a close tRNA mimic. However, YrlA lacks a free CCA end and contains a kink in the stem corresponding to the anticodon stem. Since nucleotides in the D and T stems are conserved among YrlAs, they may be an interaction site for an unknown factor. Our experiments identify YrlA RNAs as a new class of tRNA mimics.